Uruguay : Selected Issues. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2013)
Uruguay's inflation and inflation expectations exceed the inflation target, and the gap has been widening in recent years. To help bring it to the mid-point of the target, Banco Central del Uruguay (BCU) needs to maintain a tightening bias in addition to strengthening its communication. This paper examined the factors behind the composition of FDI flows to Uruguay and suggested that strong institutions and macroeconomic stability have helped attract FDI to the secondary and tertiary sectors. Flexibility of the labor market, financial deepening, and the quality of infrastructure can further this improvement.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet